Conflict monitoring and error processing: new insights from simultaneous EEG-fMRI - Iannaccone, Reto; Brandeis, Daniel (NeuroImage, 2015)
Error processing and conflict monitoring are essential executive functions for goal directed actions and adaptation to conflicting information. Although medial frontal regions such as the anterior cingulate cortex (ACC) and the pre-supplementary motor area (pre-SMA) are known to be involved in these functions, there is still considerable heterogeneity regarding their spatio-temporal activations. The timing of these functions has been associated with two separable event-related potentials (ERPs) usually localized to the medial frontal wall, one during error processing (ERN - error related negativity) and one during conflict monitoring (N2). In this study we aimed to spatially and temporally dissociate conflict and error processing using simultaneously recorded EEG and fMRI data from a modified Flanker task in healthy adults. We demonstrate a spatial dissociation of conflict monitoring and error processing along the medial frontal wall, with selective conflict level dependent activation of the SMA/pre-SMA. Activation to error processing was located in the ACC, rostral cingulate zone (RCZ) and pre-SMA. The EEG-informed fMRI analysis revealed that stronger ERN amplitudes are associated with increased activation in a large coherent cluster comprising the ACC, RCZ and pre-SMA, while N2 amplitudes increased with activation in the pre-SMA. Conjunction analysis of EEG-informed fMRI revealed common activation of ERN and N2 in the pre-SMA and divergent activation in the RCZ. No conjoint activation between error processing and conflict monitoring was found with standard fMRI analysis along the medial frontal wall. Our fMRI findings clearly demonstrate that conflict monitoring and error processing are spatially dissociable along the medial frontal wall. Moreover, the overlap of ERN- and N2-informed fMRI activation in the pre-SMA provides new evidence that these ERP components share conflict related processing functions and are thus not completely separable.